Phase-controlled synthesis of α-NiS nanoparticles confined in carbon nanorods for high performance supercapacitors - Sun, Chencheng (2015)
A facile and phase-controlled synthesis of α-NiS nanoparticles (NPs) embedded in carbon nanorods (CRs) is reported by in-situ sulfurating the preformed Ni/CRs. The nanopore confinement by the carbon matrix is essential for the formation of α-NiS and preventing its transition to β-phase, which is in strong contrast to large aggregated β-NiS particles grown freely without the confinement of CRs. When used as electrochemical electrode, the hybrid electrochemical charge storage of the ultrasmall α-NiS nanoparticels dispersed in CRs is benefit for the high capacitor (1092, 946, 835, 740 F g−1 at current densities of 1, 2, 5, 10 A g−1, respectively.). While the high electrochemical stability (approximately 100% retention of specific capacitance after 2000 charge/discharge cycles) is attributed to the supercapacitor-battery electrode, which makes synergistic effect of capacitor (CRs) and battery (NiS NPs) components rather than a merely additive composite. This work not only suggests a general approach for phase-controlled synthesis of nickel sulfide but also opens the door to the rational design and fabrication of novel nickel-based/carbon hybrid supercapacitor-battery electrode materials.